2021
DOI: 10.3389/fimmu.2021.694490
|View full text |Cite
|
Sign up to set email alerts
|

Novel Immune Infiltrating Cell Signature Based on Cell Pair Algorithm Is a Prognostic Marker in Cancer

Abstract: Tumor-infiltrating immune cells (TIICs) have become an important source of markers for predicting the clinical outcomes of cancer patients. However, measurements of cellular heterogeneity vary due to the frequently updated reference genomes and gene annotations. In this study, we systematically collected and evaluated the infiltration pattern of 65 immune cells. We constructed the Immune Cell Pair (ICP) score based on the cell pair algorithm in 3,715 samples and across 12 independent cancer types, among which,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
32
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 54 publications
1
32
0
Order By: Relevance
“…In this study, gliomas with low ALKBH5 expression showed higher proportion (66%) of IDH1 mutations compared to those with high ALKBH5 expression (21%). Previous reports showed that IDH mutations were more abundant in LGG, and the survival rate of LGG patients was higher than those with HGG ( 69 ). The low ALKBH5 expressing glioma patients (46%) also showed increased frequency of mutations in TP53 compared to the high ALKBH5 expressing group (37%).…”
Section: Discussionmentioning
confidence: 85%
“…In this study, gliomas with low ALKBH5 expression showed higher proportion (66%) of IDH1 mutations compared to those with high ALKBH5 expression (21%). Previous reports showed that IDH mutations were more abundant in LGG, and the survival rate of LGG patients was higher than those with HGG ( 69 ). The low ALKBH5 expressing glioma patients (46%) also showed increased frequency of mutations in TP53 compared to the high ALKBH5 expressing group (37%).…”
Section: Discussionmentioning
confidence: 85%
“…Tumor immunotherapy has been recently categorized into immune checkpoint inhibitors, T-cell transfer therapy, monoclonal antibodies, therapeutic vaccines, and immune system modulators, among which immune checkpoint inhibitors have become the most dazzling star. Especially with the increasing popularity of high-throughput sequencing, several new immune checkpoints have been discovered ( 32 34 ). In this paper, we systematically explored the role of CD147 as a novel immunotherapy target in the TME among 33 cancer types.…”
Section: Discussionmentioning
confidence: 99%
“…Increasing evidence has suggested that tumor-infiltrating immune cells in the TME play a critical role against cancer ( 35 , 36 ). Cancer cells are able to escape from the immune response and build complicated microenvironment in which some immune cells may promote tumor progression, invasion, and resistance to therapy ( 34 , 37 ). As the major component of the TME, tumor-associated macrophages (TAMs) are the main regulator in cancer-related inflammation ( 37 , 38 ).…”
Section: Discussionmentioning
confidence: 99%
“…We found that tubulin inhibitors can improve the e cacy of ICIs, which is consistent with previously reported ndings. It has been demonstrated that combined use of tubulin inhibitors and ICIs were successful for the treatment of non-small cell lung cancer [84-86], because tubulin inhibitors enhanced CD4 + and CD8 + T cell activity [87], inhibited Tregs [88], induced dendritic cell maturation, and increased M1 macrophages [89,90]. Our study suggests that tubulin inhibitors may "heat" the tumor immune microenvironment by activating the CXCR3 pathway, thereby improving the e cacy of ICI therapy.…”
Section: Discussionmentioning
confidence: 99%